A practical approach to tuning of SMES controller based on synchronized phasor measurements for interconnected power system with wind farms - Dechanupaprittha, S.; Li, C.; Watanabe, M.; Mitani, Y.; Hongesombut, K.; Ngamroo, I. (My University, 2008)
The high penetration of hardly predictable wind power with abrupt changes adversely affects many aspects of power system operations and control, in particular power system stability. To achieve the controller design in practice, this paper presents an approach to tuning of SMES controller based on synchronized phasor measurements for interconnected power system with wind farms. The designed controller is aimed at improving the system damping performance, meanwhile enhancing the stability of a power system. With PMUs, the most recent data of power system can be obtained for controller design. The extended simplified oscillation model is determined for detection and assessment of an approximated inter-area oscillation mode including SMES controller effects. The parameters of SMES controller are systematically tuned with less effort by tabu search towards the design specification. Finally, some simulation studies are carried out to demonstrate and confirm the applicability and effectiveness of the presented approach. © 2008 IEEE.